Wiedendiol-A inhibits cholesteryl ester binding to its transfer protein. - Wang Suke; Clemmons Anthony; Chacklamannil Samuel; Coval Stephen J; Sybertz Edmund; Burrier Robert (Acta Pharmacologica Sinica, 2016)
AIM: To study the wiedendiol-A (W-A) inhibition mechanism of plasma cholesteryl ester (CE) transfer protein (CETP) on the transfer of CE. METHODS: Using gel filtration method. RESULTS: W-A at 30 mumol.L-1 inhibited association of CE with CETP by 76% and CETP transfer activity by 81%. In addition, W-A enhanced binding of TP2, a monoclonal antibody with a CETP C-terminal epitope which is involved in CE binding, to CETP, suggesting a W-A-induced conformational change at the epitope for increased TP2 binding. When CETP activity was measured by varying high-density lipoproteins (HDL) concentration, the apparent Vmax of CE transfer was inhibited by 74% and 83% in the presence of W-A at 14 and 25 mumol.L-1, respectively, while the apparent K(m) of HDL for CETP did not change. CONCLUSION: W-A action is mediated through interaction between W-A and CETP, but not through those between W-A and lipoproteins.